2020
DOI: 10.21203/rs.2.22081/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic performance of ultrasonography, dual-phase 99mTc-MIBI scintigraphy, early and delayed 99mTc-MIBI SPECT/CT in preoperative parathyroid gland localization in secondary hyperparathyroidism

Abstract: Background: Secondary hyperparathyroidism (SHPT) usually requires parathyroidectomy when drug regimens fail. However, obtaining an exact preoperative map of the locations of the parathyroid glands is a challenge. The purpose of this study was to compare the diagnostic performance of US, dual-phase 99mTc-MIBI scintigraphy, early and delayed 99mTc-MIBI SPECT/CT in patients with SHPT.Methods: Sixty patients with SHPT who were undergoing dialysis were evaluated preoperatively by US, dual-phase 99mTc-MIBI scintigra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Zhang et al [ 25 ] found that the sensitivity of early 99m Tc-MIBI SPECT/CT was higher than delayed 99m Tc-MIBI SPECT/CT in patients with SHPT. Krakauer et al [ 26 ] reported that dual-isotope subtraction scintigraphy had higher diagnostic accuracy than dual-phase scintigraphy in patients with primary hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 25 ] found that the sensitivity of early 99m Tc-MIBI SPECT/CT was higher than delayed 99m Tc-MIBI SPECT/CT in patients with SHPT. Krakauer et al [ 26 ] reported that dual-isotope subtraction scintigraphy had higher diagnostic accuracy than dual-phase scintigraphy in patients with primary hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of 99m Tc-MIBI SPECT/CT combined with ultrasound can be further improved. It is also believed that the sensitivity of SPECT/CT imaging in the early phase is higher than that in the delayed phase [17].…”
Section: Discussionmentioning
confidence: 99%